Nanotechnology and Processes: Nano-Photovoltaic Panels as an Innovation in Energy Market - Chavaglia, José (2013)
Nanotechnology can be a powerful weapon in creating competitive advantages in the energy market, through the use of the photovoltaic nanopanels, which may reduce production costs and simultaneously meet the socio-environmental requirements. It is a way to produce clean energy. Moreover, today the adoption of nanotechnology in energy production can make this kind of energy very interesting along the years, and fractal theory may help to show the effects. Nanotechnology may, in fact, be responsible for unimaginable gains, both economically and to preserve the planet.